Thermal decomposition of N-(salicylidene)-L-leucine in static air atmosphere - Vennila, Munusamy; Manikandan, Govindasamy; Thanikachalam, Venugopal; Jayabharathi, Jayaraman (European Journal of Chemistry, 2011)
The thermal degradation of N-(salicylidene)-L-leucine was studied under non-isothermal conditions in air atmosphere. For kinetic analysis, the TG/DTA/DTG data obtained at three different heating rates were processed by Friedman, Kissinger-Akahira-Sunose, Flynn-Wall-Ozawa and Kissinger methods. The analysis indicates a complex reaction process which can be best described by the three dimensional (Ginstling-Brounshtein) model D4.